2006
DOI: 10.1111/j.1365-2672.2006.02895.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dominant microbiota of a Ghanaian fermented milk product, nyarmie, by culture- and nonculture-based methods

Abstract: Aims:  To characterize the predominant micro‐organisms in a Ghanaian traditional fermented dairy product, nyarmie, made from cows’ milk, using both culture‐ and nonculture‐based methods. Methods and Results:  Samples of nyarmie were analysed from three production sites in Accra, by determining the counts on selective culture media. The microbial diversity occurring in nyarmie was also evaluated by 16S/18S ribosomal DNA PCR amplification and denaturing gradient gel electrophoresis. Results showed that nyarmie c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Recently, numerous authors have employed a combination of culture-dependent and culture-independent methods, in order to study the behavior of the microbiota that participates in the elaboration of fermented products (Cocolin et al 2002;Prakitchaiwattana et al 2004;Nielsen et al 2005;Rantsiou et al 2005;Cocolin et al 2006;Rantsiou and Cocolin 2006;Obodai and Dodd 2006;Dolci et al 2008;Oelofse et al 2009;Kim et al 2009;Andorrà et al 2010;Lacerda Ramos et al 2010) and to understand the ecological relationship between the microorganisms and the influence of this diversity on the characteristics of the end product. As in wine, PCR-DGGE has been shown to be a reliable method for direct qualitative assessment of the yeast populations present in mezcal fermentations.…”
Section: Pcr-dggementioning
confidence: 99%
“…Recently, numerous authors have employed a combination of culture-dependent and culture-independent methods, in order to study the behavior of the microbiota that participates in the elaboration of fermented products (Cocolin et al 2002;Prakitchaiwattana et al 2004;Nielsen et al 2005;Rantsiou et al 2005;Cocolin et al 2006;Rantsiou and Cocolin 2006;Obodai and Dodd 2006;Dolci et al 2008;Oelofse et al 2009;Kim et al 2009;Andorrà et al 2010;Lacerda Ramos et al 2010) and to understand the ecological relationship between the microorganisms and the influence of this diversity on the characteristics of the end product. As in wine, PCR-DGGE has been shown to be a reliable method for direct qualitative assessment of the yeast populations present in mezcal fermentations.…”
Section: Pcr-dggementioning
confidence: 99%
“…Several reports on the enumeration and identification of LAB from different African fermented milk samples showed that mean LAB counts range between 10 7 to 10 9 CFU/ml of fermented milk (1,5,7,9). LAB may inhibit pathogens in foods by producing antimicrobial peptides and/or acid, in addition to the competitive exclusion of pathogens (2,8).…”
mentioning
confidence: 99%
“…Nyarmie has a pleasant taste and is preferred to both fresh and pasteurised milk because of its diversified properties. It can be stored for 5 days if unrefrigerated, or for several weeks if refrigerated at 4 C (Obodai and Dodd 2006). Another fermented milk produced by the Saharan tribes of West African sub-region and the inhabitants of the Mediterranean region and also of the Middle East is nono.…”
Section: Fermented Milkmentioning
confidence: 99%